First report of liposcelis bostrychophila badonnel (Psocoptera: Liposcelidae) as a museum insect pest in Malaysia - Chin, H.C.; Jeffery, J.; Ahmad, N.W.; Kiang, H.S.; Omar, B.; Othman, H.; Lim, L.H. (Penerbit Universiti Kebangsaan Malaysia, 2010)
This paper reports the infestation of psocid, Liposcelis bostrychophila Badonnel (Psocoptera: Liposcelidae) in the insect museum at Medical Entomology Unit, Institute for Medical Research, Kuala Lumpur. These tiny organisms were recognised as museum insect pest and found frequently in the insect boxes containing mosquitoes, flies, cockroaches and butterflies. They feed on dead insect specimens and cause severe physical damages to the valuable reference specimens collected in the early 20(th) century. Hence, it is important to control their population immediately to prevent them from causing further deterioration to the museum collection.